A Content Analysis of 3D Printing Policies at Academic Libraries. Issue 3 (3rd April 2017) - Horton, Jennifer
ABSTRACT: Many academic libraries are adopting 3D printing programs and researching, writing, and implementing policies for these programs. This article analyzes the content of 50 academic library 3D printing policies looking for commonalities. Five major themes emerged from the analysis: the policy's purpose, potential users of the 3D printers, 3D printing procedures, the acceptable uses of the 3D printers, and user privacy considerations. This article provides a breakdown of these five major themes.